If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(12x + -6) = 12x + 6 Reorder the terms: -1(-6 + 12x) = 12x + 6 (-6 * -1 + 12x * -1) = 12x + 6 (6 + -12x) = 12x + 6 Reorder the terms: 6 + -12x = 6 + 12x Add '-6' to each side of the equation. 6 + -6 + -12x = 6 + -6 + 12x Combine like terms: 6 + -6 = 0 0 + -12x = 6 + -6 + 12x -12x = 6 + -6 + 12x Combine like terms: 6 + -6 = 0 -12x = 0 + 12x -12x = 12x Solving -12x = 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -12x + -12x = 12x + -12x Combine like terms: -12x + -12x = -24x -24x = 12x + -12x Combine like terms: 12x + -12x = 0 -24x = 0 Divide each side by '-24'. x = 0 Simplifying x = 0
| -5(-5b+4)=14+8b | | 8+11=20 | | 3(3y-11)=-6(y+4) | | (4x)(7y)-(x)(3y)= | | 40=-10x | | 3x-2x+7x=-24 | | 12-17=139 | | 3y+9=5y-3y | | -2n+6n=16 | | -1.4=2x | | 25x^2+10x+-8= | | 8D=5F | | -8(3b+4)+(25b-5)=0 | | -6f+13=2f | | 5+4(3x-8)-2(x+6)=x-9 | | 8n+22=-2(-4n+3)+7n | | r+8.4=-0.5 | | 6=-3(r+2) | | w^2+2w=99 | | 4a=a-18 | | 2=2x-6 | | -3n+30=-6(6+6n) | | 3x^3+25=x^2+75 | | 13=3n+6-8 | | 8b-12b+10b= | | x^2+3x-72=4x | | 9l=3l+3m | | 0.66X-16=0 | | 6(w-1)=3(w+5) | | 26-5x=-7(x-4) | | (-8y-5)(7y)*y=-3 | | 5p+2=11+4p |